2016
DOI: 10.1155/2016/6241546
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Comparison of Outcomes of Early versus Delayed Carotid Artery Stenting for Symptomatic Cerebral Watershed Infarction due to Stenosis of the Proximal Internal Carotid Artery

Abstract: The aim of this study was to compare the clinical outcomes of early versus delayed carotid artery stenting (CAS) for symptomatic cerebral watershed infarction (sCWI) patients due to stenosis of the proximal internal carotid artery. We retrospectively collected clinical data of those who underwent early or delayed CAS from March 2011 to April 2014. The time of early CAS and delayed CAS was within a week of symptom onset and after four weeks from symptom onset. Clinical data such as second stroke, the National I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Current guidelines are to pursue early revascularization within 14 days of AIS [ 2 ]. Due to the increasing risk of recurrence within the first 2 weeks after the first ischemic event of a symptomatic carotid stenosis, Liu et al showed improved functional outcomes without increasing the rate of new AIS, myocardial infarction or death in the early CAS group (<1 week) compared to the delayed CAS at 1 month [ 28 ]. On the contrary, Song et al evaluated CAS for 206 patients with moderate-to-severe stenosis and found a significantly higher rate of ipsilateral stroke or death (at 30 days) of 12.8% in the early CAS group (within 14 days) compared to only 0.8% in the delayed CAS group (mean timing of CAS was 52.6 ± 36.94 days) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines are to pursue early revascularization within 14 days of AIS [ 2 ]. Due to the increasing risk of recurrence within the first 2 weeks after the first ischemic event of a symptomatic carotid stenosis, Liu et al showed improved functional outcomes without increasing the rate of new AIS, myocardial infarction or death in the early CAS group (<1 week) compared to the delayed CAS at 1 month [ 28 ]. On the contrary, Song et al evaluated CAS for 206 patients with moderate-to-severe stenosis and found a significantly higher rate of ipsilateral stroke or death (at 30 days) of 12.8% in the early CAS group (within 14 days) compared to only 0.8% in the delayed CAS group (mean timing of CAS was 52.6 ± 36.94 days) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, it was believed that the risk of early recurrent TIA or stroke after the onset of neurological symptoms is not high, so CEA should be delayed for at least 6 weeks after an onset of neurological symptoms, and operating early on a recently symptomatic “unstable” carotid plaque was associated with an increased risk of perioperative stroke [ 2 ]. In recent years, early surgical intervention within 1-2 weeks of symptom onset has been advocated for patients with symptomatic carotid artery stenosis [ 3 ]. Therefore, the timing of CEA surgery has been gradually attracted the attention of all, and studies on it have also increased gradually in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In contrast, other studies supported early CAS within their 7 or 15 days cut-off, showing no significant differences in stroke or deaths at 30 days. 6,7,17,18 A recent prospective study compared CAS to CEA when performed within the first 48 hours and found similar rates of stroke or any cause of death within 30 days (5.1% vs. 4.9%, respectively). 19 Those findings are comparable to the primary outcome rate in our emergency CAS group (5.7%).…”
Section: Discussionmentioning
confidence: 99%